Quinze ans de recherches sur l’interface entre développement durable et territoires. Un bilan réflexif - Bruno Villalba; Olivier Petit (Développement Durable et Territoires)
Fifteen years after the creation of the research network ‘Développement durable et territoires fragiles’ (Sustainable development and fragile territories) this article aims at retracing the way this research network has mobilized the notion of sustainable development, in the framework of its research activity and scientific animation This reflexive view was needed, in a context characterized by a large recognition of sustainable development as a key component of territorialized public policies, but also by the mobilization of this notion by a variety of actors, with sometimes contradictory logics.